PERAN PONDOK PESANTREN AL MUTTAQIN DALAM PEMBENTUKAN AKHLAK SANTRI DI ERA INDUSTRI 4.0 - Mat Syaifi (Center of Education Journal (CEJou), 2023)
Role means something that is played or carried out. A role is defined as an activity that is played or performed by someone who has a position or social status in the organization. Morals mean attitudes, customs, habits or systems of behavior, habits that are common in a person's personality without any coercion that occurs because of themselves. The industrial era 4.0 is an effort to transform towards improvement by integrating the online world and production lines in industry, where all production processes run with the internet as the main support. This research focuses on: the role of Islamic boarding schools in the formation of santri morals, inhibiting and supporting factors in the formation of santri morals in the industrial era 4.0? With the aim: To find out the role of the Islamic boarding school, Al Muttaqin Bugul Lor Islamic Boarding School, Pasuruan City in the formation of santri morals. To find out the inhibiting and supporting factors for santri morals at the Al Muttaqin Bugul Lor Islamic Boarding School, Pasuruan City in the industrial era 4.0. In this research, researchers use a qualitative approach. Qualitative research is research that aims to describe phenomena or events that are considered unique, actual and relevant to certain scientific disciplines. In this research, theory is only used as an analytical tool in explaining this phenomenon. Meanwhile, the type of research used in this research is descriptive. This research is divided into three stages, namely: data collection, identifying data, final stage of research.